"Ten jego emigracyjny los". O tomie opowiadań Włodzimierza Odojewskiego ...i poniosły konie - Dutka, Elżbieta (Tematy i Konteksty, 2011)
Włodzimierz Odojewski is one of the most famous émigré writers who still undertake the subject of emigration, even in his books published long after his both symbolic and real return to the homeland. Significant extension and dwelling on the subject can be observed in the book …i poniosły konie. The aim of this article is to provide an interpretation of the novels gathered in the volume (published in 2006) from the perspective of the biographical context, the rest of Odojewski’s writings, as well as his opinions on various aspects of exile. Such interpretation reveals more existential and internalized dimension of emigration but also its universal meanings. Thus, emigration is considered a metaphor of human fate.